2015
DOI: 10.1093/jac/dkv130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of β-lactam antibiotics in outpatient parenteral antibiotic therapy: treatment success, readmissions and antibiotic switches

Abstract: OPAT with β-lactam antibiotics is effective, but antibiotic switches for adverse events were more frequent with oxacillin use. Clinicians should be cognizant of the risk of readmissions and ADEs in OPAT patients, as the value of OPAT lies in reducing patient morbidity and readmissions by managing ADEs and preventing clinical failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 42 publications
4
43
0
Order By: Relevance
“…Finally, we demonstrated that patients who received nafcillin were more likely to discontinue therapy due to adverse events than were patients who received oxacillin. These data corroborate results of previous studies evaluating the tolerability of nafcillin or oxacillin among outpatients (18,19). Consensus guidelines recommend nafcillin or oxacillin as a first-line treatment for MSSA infections without a preference between the agents (5,6).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Finally, we demonstrated that patients who received nafcillin were more likely to discontinue therapy due to adverse events than were patients who received oxacillin. These data corroborate results of previous studies evaluating the tolerability of nafcillin or oxacillin among outpatients (18,19). Consensus guidelines recommend nafcillin or oxacillin as a first-line treatment for MSSA infections without a preference between the agents (5,6).…”
Section: Discussionsupporting
confidence: 87%
“…The UPMC is a tertiary-care referral center that houses highly dynamic, critically ill patients. Rates of adverse events reported here should not be directly compared to those among patients receiving OPAT (18,19). Furthermore, we cannot definitively comment on differences in the long-term tolerabilities of nafcillin and oxacillin.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Search results. The database search process identified 475 articles; 11 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) were included in the analysis of hospitalized patients, and 3 (23)(24)(25) were included in the analysis of outpatients (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%